(untitled) (International journal of medical sciences, 2025)
Immunoglobulin E (IgE) is an important antibody that plays a central role in the body's immune response to allergic diseases and parasitic infections. This review article discusses the structural properties of IgE, its synthesis, receptors (high-affinity FceRI and low-affinity Fcell/CD23), protective mechanisms against allergens and parasitic antigens, as well as its pathogenetic role in atopic diseases (atopic dermatitis, allergic rhinitis, bronchial asthma, anaphylaxis). Population studies conducted in recent years have shown that an increase in the level of total and allergen-specific IgE is a major factor in the epidemiological increase in allergic diseases worldwide. In industrialized countries, sensitization is observed in 25-40% of the population, with total IgE levels exceeding 100-150 kU/L, and this figure is even higher in children and young people. In tropical regions, polyclonal IgE hyperimmunoglobulinemia (up to 10,000-30,000 KU/L) associated with helminth infections is characteristic. The pathogenesis section provides an in-depth analysis of the relationship between IgE synthesis and genetic (IL4RA, STAT6, FCER1A, IL13 gene polymorphisms), epigenetic and environmental factors (allergen exposure, microbiome disruption, "hygiene hypothesis"), the central role of the Th2-oriented immune response, mast cell and basophil degranulation, eosinophil activation, and mechanisms of late-type allergic reactions. New roles of IgE in neuroimmune and tissue remodeling processes (e.g., autoimmune IgE and anti-FceRl antibodies in chronic urticaria) are also discussed. The diagnostic department uses modern laboratory methods such as total IgE, allergen-specific IgE (ImmunoCAP, ISAC chip technology), skin prick tests, component diagnostics, basophil activation test (BAT), as well as molecular Allergology approaches (CRD component-resolved diagnostics) and their clinical sensitivity and specificity are described in detail. The treatment section presents the efficacy, indications, and long-term outcomes of allergen-specific immunotherapy (ASIT/SCIT and SLIT), biological drugs, anti-IgE monoclonal antibody omalizumab (FDA approved in 2003, currently used in children over 6 months of age), new generation anti-IgE drugs (ligelizumab, quilizumab), anti-IL-4Ra (dupilumab), anti-IL-5/IL-5R (mepolizumab, reslizumab, benralizumab), and future potential targets (anti-TSLP, anti-IL-33) based on scientific evidence.